KATRIN: status and prospects for the neutrino mass and beyond. (1st October 2022) - Aker, M; Balzer, M; Batzler, D; Beglarian, A; Behrens, J; Berlev, A; Besserer, U; Biassoni, M; Bieringer, B; Block, F; Bobien, S; Bombelli, L; et al.
Abstract: The Karlsruhe Tritium Neutrino (KATRIN) experiment is designed to measure a high-precision integral spectrum of the endpoint region of T2 β decay, with the primary goal of probing the absolute mass scale of the neutrino. After a first tritium commissioning campaign in 2018, the experiment has been regularly running since 2019, and in its first two measurement campaigns has already achieved a sub-eV sensitivity. After 1000 days of data-taking, KATRIN's design sensitivity is 0.2 eV at the 90% confidence level. In this white paper we describe the current status of KATRIN; explore prospects for measuring the neutrino mass and other physics observables, including sterile neutrinos and other beyond-Standard-Model hypotheses; and discuss research-and-development projects that may further improve the KATRIN sensitivity.